The impact of altitude on infant health in South America - Wehbya, George L. (2010)
Several studies report that altitude reduces birth weight. However, much remains unknown about effects in various altitude ranges and about the heterogeneity in altitude effects by fetal health endowments. This study estimates the effects of altitude in South America on the means and quantiles of birth weight and gestational age separately for two large samples born at altitude ranges of 5 to 1,280mand 1,854 to 3,600 m. The study finds significant negative altitude effects on birth weight and gestational age in the low-altitude sample and on birth weight in the high-altitude sample. Altitude effects are larger for infants with very low fetal health endowments. The study finds differences in the effects of several inputs such as socioeconomic status and maternal fertility history and health between the two altitude samples. The study highlights the importance of adverse altitude effects on infant health when evaluating the costs and returns of policies that change the number of individuals who reside at higher altitude in both low and high altitude ranges.